Influence of the K+/Ca2++Mg2+ ratio in the yield of zucchini (Cucurbita pepo L.) - Rueda-Luna, Rolando; Reyes-Matamoros, Jenaro; Romero-Hernández, Miriam; Hernández-Loma, Raymundo; Cruz-Montalvo, Abel (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
Zucchini (Cucurbita pepo L.) is a widely cultivated vegetable that plays a significant role in global food production. Its yield and nutritional composition are influenced by various agronomic factors, including the availability and balance of essential nutrients. Among these, the cationic ratio of potassium (K+), calcium (Ca2+), and magnesium (Mg2+) in the nutrient solution is critical for plant growth and productivity due to their interactive effects on absorption and transport. The objective of this study was to evaluate the impact of different K+/Ca2++Mg2+ ratios on the yield and mineral composition of zucchini leaves. The experiment was conducted under greenhouse conditions using a factorial design with two commercial varieties (Zuchinni Gray and Ambrosia) and five nutrient solutions with different cation ratios (K+/Ca2++Mg2+; 0.2, 0.6, 1.0, 1.4, and 1.8). Plants were grown in polyethylene containers filled with red tezontle substrate. The results showed that Ambrosia exhibited a higher total yield compared to Zuchinni Gray. The K+/Ca2++Mg2+ ratios of 1.4 and 1.8 significantly increased total production, while the ratio of 1.4 enhanced calcium absorption. However, no significant differences were observed in potassium and magnesium content in the leaves. These findings highlight the importance of optimizing the cationic balance in the nutrient solution to improve zucchini productivity and mineral composition.